2020
DOI: 10.6018/reifop.396741
|View full text |Cite
|
Sign up to set email alerts
|

Análisis correlacional de los factores incidentes en el nivel de competencia digital del profesorado

Abstract: Conocer los factores que inciden en la competencia digital docente es imprescindible para que los centros educativos elaboren planes formativos adaptados a las necesidades del alumnado actual. El objetivo de investigación se centra en conocer la incidencia que ejercen en el nivel de competencia digital algunos factores inherentes a la función docente: sexo, edad, experiencia, etapa educativa y nivel de formación. Se ha empleado un diseño cuantitativo sustentado en un enfoque descriptivo y correlacional, con un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 16 publications
1
15
0
23
Order By: Relevance
“…Some researchers have developed a model that integrates the technology acceptance model (TAM) with the updated DeLone and McLean's model (DL & ML) and have found that among the factors affecting students' intention to explore such new technology is the quality of this type of m-learning [31]. Prior to introducing new digital technologies for use by students, the factors that affect the effectiveness and efficiency of teaching using these technologies must be known [32].…”
Section: Related Studies On M-learningmentioning
confidence: 99%
“…Some researchers have developed a model that integrates the technology acceptance model (TAM) with the updated DeLone and McLean's model (DL & ML) and have found that among the factors affecting students' intention to explore such new technology is the quality of this type of m-learning [31]. Prior to introducing new digital technologies for use by students, the factors that affect the effectiveness and efficiency of teaching using these technologies must be known [32].…”
Section: Related Studies On M-learningmentioning
confidence: 99%
“…The ability to implement new digital learning solutions requires lifelong learning skills [16][17][18]. The issue of updating knowledge and skills mainly concerns the digital competence of teachers [19][20][21].…”
Section: Lifelong Learning In Digital Competencementioning
confidence: 99%
“…Furthermore, the interest expressed in previous research articles about the influence of different variables in the teacher training, e.g., age, gender, etc. [40,41], was not considered in this analysis since this is out of the scope of the article. Therefore, these aspects will be considered for the future, thereby continuing the research line initiated through the methodology proposed in this study.…”
Section: Discussionmentioning
confidence: 99%